Changes in Aboriginal Patient Experiences of Care in NSW Public Hospitals From 2014 To 2018: The NSW Patient Survey Program - Tran, Hoang Ngoc Bich (International Journal of Population Data Science, 2020)
Introduction New South Wales is home to more Aboriginal people than any other state or territory in Australia. While much is known about social and health status among these Aboriginal people, less is known about their experience of healthcare. Objectives and Approach BHI produces independent reports and information about the performance of the NSW healthcare system. In collaboration with the NSW Ministry of Health Centre for Aboriginal Health, our report explored trends in Adult Admitted Patient Survey in public hospitals for a range of measures from 2014 to 2018 for Aboriginal and non-Aboriginal patients. Administrative survey data were used to establish a sample frame, send questionnaires to a random sample of patients within three months following discharge and assess representativeness of respondents. We used logistic regression models, adjusted for age, sex, education and language spoken at home, to estimate the change of experience over time for both populations. Results There were 122,626 patients who shared their experiences each year from 2014 to 2018, among them, 4% identified themselves as Aboriginal. Aboriginal respondents in the survey were similar in age, sex, country of birth and stay type to the administrative sampling data. In 2018, 70% of Aboriginal patients said they would “speak highly” of their experience compared to 79% of non-Aboriginal patients. Across 51 measures, experience of care improved significantly for 39 measures among non-Aboriginal patients, and four among Aboriginal patients (privacy, experience with nurse, communication with patients). Conclusion / Implications Aboriginal patients have less positive experience of the hospital care in general and there has been little improvement in their experience in recent years. Identifying areas of less positive experiences where health professionals can play a role individually or in a team could minimise disparities in experience of care.